Weight distribution algorithm for global ship analysis in preliminary design stage. Issue 3 (13th May 2022) - Lim, Chaeog; Han, Ik-seung; Park, Byeong-cheol; Oh, Sang-jin; Kim, Gi-yong; Shin, Sung-chul
Abstract: Structural analysis, based on a global ship model, is vital for examining the structural strength and safety of a hull. In the "NASTRAN" global ship model, only the structural members and cargo tank of a ship are modeled and the outfit, electric system, and other tanks and liquid are omitted from the model. The additional weight of these omitted elements, however, constitutes part of the light weight of the ship and must be considered in conducting an accurate structural analysis of the ship. Generally, the weight of these omitted elements is calculated using the trim and stability information of the ship and is then added to the model. In such cases, the center of gravity of the global ship model, which now includes the weight of these omitted elements, must be adjusted to the target center of gravity required for the analysis. In this study, an algorithm was developed to satisfy the target center of gravity while distributing the weight of these omitted elements to the global ship model using Gaussian elimination. The algorithm was developed using C#, and its accuracy was verified by applying it to the global ship models. Graphical Abstract: